Respon Kedelai Kultivar Kipas Putih dan Wilis pada Kadar Air Tanah yang Berbeda Terhadap Pertumbuhan dan Hasil - Cut Nur Ichsan; Mardhiah Hayati; Syarifah Putri Mashtura (Jurnal Agrista, 2010)
Response of Soybean Cultivars Kipas Putih and Wilis to Soil Moistureon Growth and YieldABSTRACT. The research has been made to explain relationship between soil moisture and the growth and yield of soya bean variety Willis and Kipas Putih. Block randomized design with factor type 2x4 and three repetition has use to analize the effect of soil moisture on those variety. The parameter use in this research were hight of the plan, plan growing rate, number of pod, length of the root, drying biomassa, and dry seed per plan. The research result showed that variety have very significant difference on high of plan 45 days after planting and dry biomassa per plan , have significant difference on growing rate after 45 after planting, number of pod, and has unsignificant difference on high of the plan 14 and 28 after planting, growing rate 28 and 56 days after planting, number of pods,length of the root, and dry seed per plan. Variety willis gives better grow and yield than Kipas Putih. Soil moisture has very significant differency on high of the plan 14 and 28 after planting and growing rate 28,45,56 after planting, number of regume per plan, number of filling pods per plan, length of the root, and weight of dry seed per plan. Field capacity level of soil moisture gives growth and yield better than others. Relationship between variety and soil moisture is very significant on hight of the plan 45 days after planting, growth and yield the best showed by variety Willis and field capacity level of soil moisture.